Entrepreneur and self management - Lucky, Esuh Ossai-Igwe; Minai, Mohd Sobri (2013)
Until now, many entrepreneurs remain in effective as a result of their inability to management their self, as a powerful factor to entrepreneur’s personal success and firm performance, self management has remain unexploited in both academic and practical field of small business and entrepreneurship management.Thus, until date, research in this area has only focus on entrepreneurship and time management.Therefore, within the context of this paper, the present paper examines self management in relation to entrepreneur. The paper argues on the crucial role of self management for entrepreneurs’ success and firm performance and noted that it deserves urgent and serious consideration in entrepreneurial discourse and thus should not be neglected.